Studies of Neotropical crickets: New Paragryllina taxa (Orthoptera: Phalangopsidae) with comments on several previously described species - Cadena-Castañeda, Oscar J.; Páez, Geraldine; Buitrago, Oscar; Quintana-Arias, Ronald Fernando; Tavares, Gustavo Costa (Zootaxa, 2021)
Here, we contribute to the study of the subtribe Paragryllina, recovering as valid, taxa previously described as subfamilies or tribes of Paragryllidae (currently considered as a synonym of Phalangopsidae), but which are well delimited and can be considered as genera groups of Paragryllina: Paragryllae n. stat., Rumeae n. stat., and Benoistellae n. stat.. Alfarogryllus n. gen. is described to accommodate Eneoptera panoplos. Paragryllus is divided into three subgenera: Paragryllus s.s., Melloius n. subgen., and Souzaius n. subgen.. Paragryllus (Paragryllus) lyrae n. sp. (from southern Costa Rica) is described. Paragryllus cocos is considered as nomen nudum; Paragryllus arima n. syn. is synonymized under Paragryllus insolitus and transferred to the genus Ectecous, as the new combination Ectecous insolitus n. comb.; Eneoptera spodios n. syn. is synonymized under Lerneca digrediens, remaining only the Eneoptera species known before the contribution by Otte (2006). Dambachia is included in the subtribe Paragryllina. This genus stands out for the modification of its subapical spur of the hind tibia and its asymmetric genitalia. Keys for the genera and genera groups of Paragryllina, and subgenera of Paragryllus are provided. Finally, the taxonomy of Neotropical crickets is discussed.